Effects of acute moderate hypoxia on anaerobic capacity in endurance-trained runners - Friedmann, B.; Frese, F.; Menold, E.; Bärtsch, P. (European Journal of Applied Physiology, 2007)
While there is some controversy whether anaerobic capacity might be improved after altitude training little is known about changes in anaerobic capacity during hypoxic exposure in highly trained athletes. In order to analyze the effects of acute moderate normobaric hypoxia on anaerobic capacity, 18 male competitive triathletes, middle- and long-distance runners ([(V)\dot]O2max 67.4 ±3.8 ml kg min-1)(VO2max67438mlkgmin-1) performed 2 supra-[(V)\dot]O2maxVO2max treadmill runs with the same speed, one in normoxia and one after 4 h exposure to normobaric hypoxia (FiO2 0.15), for estimation of their maximal accumulated oxygen deficit (MAOD) and measurement of peak capillary lactate and peak capillary ammonia concentration. MAOD was not significantly different in normoxia and in moderate hypoxia while time to exhaustion and accumulated O2 uptake were significantly (P < 0.001) reduced in hypoxia compared to normoxia by 28 and 45%, respectively. The reduction in time to exhaustion was significantly correlated to the decrement in accumulated O2 uptake (R = 0.730, P = 0.001). In hypoxia, there was a tendency for peak capillary lactate concentration to be decreased compared to normoxia (12.9 ± 2.1 vs. 13.8 ± 2.2 mmol l-1, P = 0.082); peak capillary ammonia concentration was significantly decreased in hypoxia (97 ± 52 vs. 121 ± 44 µmol l-1, P = 0.032). In conclusion, anaerobic capacity is not significantly changed during acute exposure to moderate hypoxia in endurance-trained athletes. The performance reduction during all-out exercise of short duration has to be attributed to the decrement in aerobic capacity.